تقصي انتشار دودة اللوز الشوكية Earias insulana (Boisd.)على البامياء في المنطقة الساحلية ودراسة بعض صفاتها الشكلية ودورة حياتها (Latakia University Journal -Biological Sciences Series, 2019)
Erias insulana (Boisd.))Lepidoptera: Nolidae( is an important pest affecting okra. In the 2018 season, a field survey was carried out in Lattakia and Tartous to determine the infestation rates of spiny bollworm. The insect biology on okra fruits was studied under laboratory conditions, at 27 ± 2 °C and relative humidity of 65 ± 5%, and a photoperiod of 16:8 (L:D) hours at Agricultural Scientific Research Center in Lattakia. The findings showed prevalence of spiny bollworms in all studied localities . The average infestation rate was 18.64 % in Tartous and 10.91 % in Lattakia. The results of the biological study revealed  that the incubation period from eggs to emergence of adults lasted 22 to 25 days. The female survival was 20 ± 1.41 days, laying 209 to 235 eggs, while male survival lasted 15 to 20 days . The highest mortality rate was in the first larval instar (20%).   تعدّ دودة اللوز الشوكية (Boisd.) Earias insulana ( Lepidoptera: Nolidae) من الآفات المهمة التي تصيب نباتات البامياء. تم في موسم 2018 تنفيذ مسح حقلي في مناطق زراعة البامياء في محافظتي اللاذقية وطرطوس، وحساب نسبة الإصابة بالحشرة. كما تمت دراسة حياتية الحشرة ضمن ظروف محددة عند درجة حرارة 27 ±2 °س، ورطوبة نسبية  65±5% وإضاءة 16ضوء/8 ظلام في مركز البحوث العلمية الزراعية في اللاذقية. أظهرت نتائج الدراسة انتشار دودة اللوز الشوكية في المنطقة الساحلية, وكان متوسط نسبة الاصابة (18.64%) في محافظة طرطوس و(10.91%) في محافظة اللاذقية. كذلك بينّت نتائج دراسة حياتية الحشرة على ثمار نبات البامياء ( بلدية حمراء), أن المدة التي استغرقتها الحشرات من وضع البيض وحتى خروج البالغات ترواحت ما بين 22 إلى 25 يوماُ, وكان متوسط مدة بقاء الإناث, 20±1.41 يوماً, وضعت خلالها من 209 إلى 235 بيضة, بينما استغرقت مدة بقاء الذكور من 15 إلى 20 يوماً. ظهرت أعلى نسبة للموت خلال دورة حياة الحشرة في العمر اليرقي الأول (20%).